Improved Monitoring of Low-Level Transcription in Escherichia coli by a β-Galactosidase α-Complementation System - Guo, Yan; Hui, Chang-Ye; Liu, Lisa; Zheng, Hao-Qu; Wu, Hong-Min (Frontiers in Microbiology, 2019)
Genetically encoded reporter proteins are important and widely used tools for the identification and capture of a promoter, tracking the dynamic behavior of transcription, and the quantification of promoter activity. The sensitivity of the reporter gene is a critical factor for an ideal reporter system, because weak transcriptional signal has usually failed to be detected using classical reporters. In this study, we present a novel reporter system for improved monitoring of transcription in E. coli based on β-galactosidase α-complementation. In this reporter system, the β-galactosidase activity resulting from assembly of a reporter lacZα and an existing α-acceptor in vivo serves as a measure of transcriptional activity. To validate the potential of the lacZα-derived reporter system, both the moderately strong lac promoter and weak pbr promoter were chosen as the detection promoters. Due to the efficient expression profile of the reporter lacZα peptide, the detection sensitivity of lacZα-derived reporter system was significantly higher than that of a traditional fluorescent protein reporter system in both monocistronic and dicistronic reporter constructs. More importantly, due to a slight metabolic burden resulting from the production of lacZα, the detection sensitivity and strength from the upstream fluorescent protein reporter were not nearly as affected in the lacZα-derived dual reporter systems. The lacZα-derived reporter system may prove to be a valuable tool for monitoring low-level transcription in vivo. It may also allow a high sensitivity analysis and simultaneous assessment of transcription in a population (using β-galactosidase activity) and in single cells (using fluorescent protein) based on a dual reporter system with lacZα as a downstream reporter.